Evaluation of Makassar City Government Recover Program - Muhammad Guntur; Andi Cudai Nur; Triyani Setiawan (Iapa Proceedings Conference, 2022)
This study aims to determine and analyze the Makassar Recover Program of the Makassar City Government, using a qualitative approach. Collecting data using observation, interview, and documentation techniques. Data obtained from processing results using interactive model analysis includes data collection, data condensation, data presentation, and conclusion testing. The results showed that the Makassar City Government's evaluation of the Makassar Recover program was based on four dimensions including context, input, process, and product, on health immunity, social adaptation, and economic recovery. The context dimension shows that the Makassar Recover program on health immunity and social adaptation runs optimally, but the economic recovery program shows results that are not optimal. The input dimension shows that the availability of human resources and budget. The process dimension shows that the Makassar Recover program is implemented according to standard operating procedures and strict regulations. The product dimension shows that the Makassar Recover program has resulted in a synergistic role between the community and the government in tackling the impact of the COVID-19 virus as well as social adaptation, but the economic recovery has not shown satisfactory results. The determinant factors in this study indicate the existence of strict regulations, resources that include the quality of human resources and budgets, as well as culture in realizing Makassar Recover in Makassar City.